Recent Advances in Nanoparticle-Based Corrosion Inhibition of Metals: A Review - Silas Oseme Okuma (NIPES - Journal of Science and Technology Research, 2025)
Increasing concerns over the environmental impacts of conventional corrosion inhibitors have driven research toward more sustainable solutions. Nanotechnology has emerged as a promising eco-friendly alternative, with nanoparticles offering superior corrosion inhibition due to their high surface-area-to-volume ratio and tunable surface functionalities. This review evaluates the performance of nanoparticles synthesised through various methods, particularly green synthesis, in mitigating metal corrosion across industrial applications. Studies have reported inhibition efficiencies ranging from 55% to as high as 98.5% in aggressive media such as 1 M HCl and 3.5% NaCl, depending on nanoparticle type, size, and functionalisation. Nanoparticles such as ZnO, TiO₂, AgNPs, and hybrid composites have demonstrated strong protective capabilities by forming adherent passive films that block corrosion pathways.The review discusses synthesis strategies, adsorption mechanisms, and environmental implications while identifying key parameters influencing performance. It also highlights ongoing challenges in reproducibility, scalability, and standardisation and proposes future directions for improving nanoparticle-based corrosion protection, especially under aggressive environmental conditions.
Keywords: Nanoparticles; Synthesis; Biocompatibility; Anticorrosion; Scalable; Corrosion Inhibitor